A Comparison of Contractile Properties and Acute Muscle Fatigue Response in Adult Females with Non-Specific Chronic Low Back Pain - Hyungwoo Lee; Seungwon Lee; Chanki Kim; Kyoungkyu Jeon (Bioengineering)
This study examined the erector spinae contractile properties, trunk isokinetic strength, and differences in acute muscle fatigue response after exercise in young females with and without non-specific chronic low back pain (NSCLBP). This study evaluated participants using tensiomyography and isokinetic trunk strength tests. An independent t-test compared the control group and the NSCLBP group, while a two-way mixed ANOVA analyzed differences in the erector spinae’s acute muscle fatigue response before and after exercise within and between groups. The results of the tensiomyography indicated that the NSCLBP group exhibited significantly lower Dm and Vc (p < 0.05) compared to the control group, while Tc showed no significant difference between groups. Significant differences in all variables were observed between the groups in the isokinetic trunk strength test (p < 0.05). Furthermore, the two-way mixed ANOVA revealed significant group main effects in Dm and Vc of the erector spinae (p < 0.05). This study found that non-specific chronic low back pain is linked to a decrease in Dm, Vc, and trunk isokinetic strength in both extensor and flexor muscles. It suggests that future research should further investigate the acute muscle fatigue response in individuals with and without NSCLBP.